1998
DOI: 10.1099/00222615-47-12-1105
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Putative Virulence Factors of Serratia Marcescens with Respect to O and K Serotypes

Abstract: Serratia marcescens serotypes 06:K14, 08:K14 and 028:K28 are common in the natural environment, but rare in hospitals. Serotypes 014:K14 and 027:K14 predominate among clinical strains, but not in the environment, suggesting that the latter serotypes may be more suited for survival in the clinical setting. Consequently, 469 epidemiologically distinct strains of S. marcescens were tested for various putative virulence factors and analysed for associations with serotype. The factors positively associated with ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 13 publications
0
51
1
Order By: Relevance
“…This was further confirmed by testing the adherence of E. coli O55:K39 serotype to tracheal explants, which proved the efficiency of using formalin as a disinfectant in poultry farms. Aucken and Pitt (1998) found that the only positive association for the dominant clinical Serratia marcescens serotype O14:K14 was related to adherence. They indicated the importance of the initial colonization of the host as a prerequest for the establishment of infection.…”
Section: Discussionmentioning
confidence: 98%
“…This was further confirmed by testing the adherence of E. coli O55:K39 serotype to tracheal explants, which proved the efficiency of using formalin as a disinfectant in poultry farms. Aucken and Pitt (1998) found that the only positive association for the dominant clinical Serratia marcescens serotype O14:K14 was related to adherence. They indicated the importance of the initial colonization of the host as a prerequest for the establishment of infection.…”
Section: Discussionmentioning
confidence: 98%
“…Of these strains, three are clinical isolates and two are environmental. It has long been observed that nonpigmented antibiotic-resistant strains of S. marcescens are much more common in the clinical setting than in the natural environment (Aucken & Pitt, 1998;Carbonell et al, 2000;Grimont & Grimont, 1978). There is no obvious reason for the prevalence of non-pigmented clinical strains, Fig.…”
Section: Differences In Pig Cluster Regulationmentioning
confidence: 99%
“…Due to the metabolic capacity of S. marcescens strains to degrade petroleum, these strains have been used alone or in microbial consortia, aiming at the recovery of environments impacted by petroleum spills and derivatives (Wongsa et al, 2004;Ortega-González et al, 2013;Silva et al, 2015). Serratia marcescens is able to survive in inhospitable environments, presenting resistance to antiseptics, disinfectants and antibiotics (Aucken & Pitt, 1998;Doi et al, 2004;Iguchi et al, 2014). The ability to metabolize different xenobiotics, produce bioactive compounds as well as colonize different environments are among the characteristics that gives to this species multiple abilities and a great biotechnological and commercial potential.…”
Section: Introductionmentioning
confidence: 99%